A solvothermal method for synthesizing monolayer protected amorphous calcium carbonate clusters - Sun, S.; Gebauer, Denis; Cölfen, H. (The Royal Society of Chemistry, 2016)
© 2016 The Royal Society of Chemistry.A solvothermal method was developed for synthesizing organic monolayer protected amorphous calcium carbonate clusters using 10,12-pentacosadiynoic acid as ligand, ethanol as solvent and NaHCO3 decomposition as CO2 source, which can be extended to synthesize other monolayer protected mineral clusters.